Gathering "tea" - from necessity to connectedness with nature. Local knowledge about wild plant gathering in the Biosphere Reserve Grosses Walsertal (Austria) - Grasser Susanne; Schunko Christoph; Vogl Christian R (BMC, 2012)
Abstract Background Wild plant gathering is an essential element in livelihood strategies all over the world. However due to changing circumstances in Europe, the reason for gathering has altered from one of necessity in the past to a pleasurable activity today. Wild plant gathering has therefore also received renewed attention as a form of intangible cultural heritage expressing local preferences, habits and man's relationship with nature. In the Biosphere Reserve Grosses Walsertal (Austria), local people's knowledge of the gathering of wild plants and their perception of their own gathering activities are being documented. The focus of this paper is on the uses of herbal teas and the informal guidelines for gathering plants that have been issued by the Bergtee (mountain tea) association. Methods Thirty-six free-list interviews were conducted with subsequent semi-structured interviews and three focus group meetings held with members of the Bergtee association. Participatory observation (gathering and processing plants, mixing and marketing tea) also allowed for greater understanding of what had been reported. Results In total, 140 different gathered plant species were listed by respondents. Herbal tea is the most frequently mentioned use. The Bergtee association, founded by a young man and two middle-aged women in the valley, is a good example of the link between biological and cultural diversity, with the aim of sharing the biosphere reserve's natural treasures as well as local plant-related knowledge in the form of herbal tea products. The association's informal guidelines for gathering reflect people's attitude to nature: monetary income does not play a major role in gathering plants; instead people's appreciation of the value of the nature around them is to the fore. Conclusions Gathering wild plants can be seen as an expression of people's regional identity. The conscious appreciation of nature and related local knowledge is crucial for the sustainable conservation and use of the Biosphere Reserve's resources.